SEX DIFFERENCES IN CARDIOMYOCYTE CONNEXIN43 EXPRESSION - Stauffer, Brian L. (2011)
Decreases in cardiac connexin43 (Cx43) play a critical role in abnormal cell to cell communication and have been linked to the resistance of the female heart to arrhythmias. We therefore hypothesized that Cx43 expression would be greater in female cardiomyocytes than male cardiomyocytes under pathologic conditions. Adult ventricular myocytes were isolated from male and female rats and treated with phenylephrine, a well established pathologic stimulus. Cx43 gene and protein expression was determined. microRNA-1 expression, a microRNA known to control Cx43 protein expression in cardiomyocytes, was also determined. Cx43 mRNA and protein levels were significantly higher in the female cardiomyocytes than the male cardiomyocytes (mRNA: 1.4-fold; Protein: 5-fold, both p< 0.05) under both basal and pathologic conditions. Phenylephrine treatment increased Cx43 expression only in female cardiomyocytes. Cx43 phosphorylation, a marker of preserved Cx43 function, was also higher (P<0.05) and microRNA-1 expression was lower (P<0.05) in the female cardiomyocytes after phenylephrine treatment. microRNA-1 expression was unchanged by phenylephrine treatment in male cardiomyocytes. Thus, a sex-difference in microRNA-1 may be responsible for the sex-difference in Cx43 expression in cardiomyocytes under pathologic conditions. Taken together our results demonstrate a sex-difference in Cx43 expression and site specific phosphorylation that favors cardioprotection in female cardiomyocytes.